Bis(Naphthalene Imide)diphenylanthrazolines: A New Class of Electron Acceptors for Efficient Nonfullerene Organic Solar Cells and Applicable to Multiple Donor Polymers. Issue 8 (8th January 2015) - Li, Haiyan; Earmme, Taeshik; Subramaniyan, Selvam; Jenekhe, Samson A.
<x xml:space="preserve">Abstract</x> Unlike universally applicable fullerene derivatives, current nonfullerene electron acceptors are rarely effective with more than one donor polymer in bulk heterojunction (BHJ) solar cells. A novel class of nonfullerene electron acceptors, bis(naphthalene imide)‐3, 6‐diphenyl‐trans‐anthrazolines (BNIDPAs), that is applicable and yields efficient photovoltaic devices with multiple donor polymers, including a thiazolothiazole–dithienosilole copolymer (PSEHTT) and benzodithiophene copolymers (PBDTT‐FTTE and PTB7) is reported. Photovoltaic devices composed of the BNIDPA‐butyloctyl (BO) acceptor with PSEHTT, PBDTT‐FTTE, and PTB7, respectively, have power conversion efficiencies of 3.0%–3.1% with high open‐circuit voltages of ≈1.0 V. In contrast, BHJ devices composed of BNIDPA‐DT acceptor with larger 2‐decyltetradecyl chains and the same donor polymers have substantially reduced bulk electron mobility and reduced photovoltaic efficiencies of 1.3%–1.7%, which highlight the critical role of the size of alkyl chains appended onto nonfullerene electron acceptors. The present results provide a rare example of nonfullerene electron acceptors that are capable of pairing with multiple donor polymers to achieve efficient BHJ solar cells.